SELF-ESTEEM OF COMMUNITY-BASED ELDERLY AND ASSOCIATED FACTORS: A POPULATION-BASED STUDY - Michelle Couto Salerno; Alisson Fernandes Bolina; Flavia Aparecida Dias; Nayara Paula Fernandes Martins; Darlene Mara dos Santos Tavares (Universidade Federal do Paraná, 2015)
The aim was to assess the self-esteem of community-based elderly and verify its association with socio-demographic and health variables. The epidemiological survey was held in the urban region of Uberaba, a city in the state of Minas Gerais, with 980 elderly people. The Rosenberg Self-Esteem, Katz, Lawton and Short Geriatric Depression Scales were used and, for descriptive analysis, the Mann-Whitney and Kruskal-Wallis tests, Spearman's correlation and multiple linear regression were used (p<0.05). The data were collected between August 2012 and March 2013. The female gender was predominant, 70-80 years, married, income one minimum wage, between four and seven years of education, who lived with their children. The median number of illnesses was five. The median self-esteem score was ten. The predictors of worse levels of self-esteem were higher age (p<0.01), lower education (р=0.021) and signs of depression (р<0.001). The community-based elderly presented high self-esteem and signs of depression were the main predictor of low self-esteem.